Effect of Organizational Culture and Leadership on Employee Performance at the Regional Office the Ministry of Religion of West Sumatra Province with Work Motivation as an Intervening Variable - ., Azmi; ., Heryanto (Archives of Business Research, 2019)
Influence of leadership on work motivation, influence of motivation on performance, influence of organizational culture on performance through work motivation and influence of leadership on performance through work motivation. This research is a quantitative research with a type of path analysis research. The Regional Office of Religion of West Sumatra Province. The sample in this study was 89 respondents. The research variable consists of free variables namely work culture and leadership, intervening variables of work motivation, and dependent variables namely performance. The instrument is a questionnaire sheet. The collected data were analyzed using the Partial Least Square (PLS) equation. Based on data analysis, there is a significant influence between organizational culture on motivation, leadership on performance, leadership on work motivation, motivation on performance, organizational culture on performance, and organizational culture on performance. through work motivation and leadership on performance through work motivation.